TO THE QUESTION ON THE ECONOMIC RESEARCH USING ELECTRONIC DATA BASES - Yulia A. Kreminskaya; Dmitry A. Suslov (Статистика и экономика, 2016)
This article discusses problems of information provision of operative-investigativeactivities, aimed at curbing economiccrimes. The central place in the article is devoted to the use of special techniquesand algorithms for economic researchwith the use of electronic databases, and increasing the effectiveness and quality of evaluations.